Programa de capacitación a los usuarios que utilizan las tarjetas de créditos del Banco de Guayaquil - Mora Morán, Marlon (2011)
This research was conducted, it was considered necessary to help train those responsible for the Management and Training Branch of the Bank of Guayaquil, Quevedo. It is therefore necessary to design a system of continuous training, with a view to training strategies are implemented that allow the user to generate client and cardholder a more global view of services, from information and knowledge of current system financial, mission, functions, structure, services, procedures, advantages, disadvantages and potential legal proceedings workforce development. For which the following aims. Design a continuous training program for clients of Banco Guayaquil on credit cards. Making a diagnosis of the Bank's credit cards Guayaquil. Identify electronic products offered by the institution. Noted the requirements for issuing a credit card. Knowing the type of advice provided by the institution to customers on managing credit cards. The sample consisted of customers of the bank cardholders Guayaquil giving a sample of 332 customers, which were surveyed to identify the needs and views on the use of the cards. 100% of customers consider it necessary internal and external training in order to acquire new knowledge, skills and appropriate wood to use credit cards. It is also important to make the training plan with purpose and structure. The budget is designed for internal training for a total of $ 3.989,04 per year. External training is carried out by external audit agencies, as Superintendent of companies and other domestic financial institutions by internal instructors and individuals hired by the institution.